CHSE-based healthy culinary as a strategy to increase consumer purchase intention in Malang City - Rulli Krisnanda; Aprillia Rachmadian (Universitas Merdeka Malang, 2022)
The COVID-19 pandemic has made several culinary entrepreneurs in the city of Malang had a decline in turnover due to limited of tourists entering the city of Malang. Cleanliness efforts and guidelines called CHSE by the Ministry of Tourism and Creative Economy are published to help address these impacts. The specific purpose of this study is to analyze the culinary needs of consumers in the city of Malang during a pandemic with the aim of making a strategy that can increase purchase intention. The urgency of this research is to get a strategy to increase consumer purchase intention in Malang City for culinary entrepreneurs in Malang city based on consumer preferences for culinary in the new-normal era. The method used is need analysis. The Mean and Standard Deviation are used to calculate the average level of need for which CHSE-based culinary aspects are the most dominant. The findings from this study are that the culinary aspects that dominate purchase intention are cleanliness, safety and environmental (environment/green product).